2017
DOI: 10.1097/igc.0000000000001086
|View full text |Cite
|
Sign up to set email alerts
|

Therapy Modalities, Prognostic Factors, and Outcome of the Primary Cervical Carcinosarcoma: Meta-analysis of Extremely Rare Tumor of Cervix

Abstract: In due course of presentation, the tumor stage has a great importance because it is the only independent factor for prognosis. Surgery followed by adjuvant radiotherapy with or without chemotherapy seems to be related with better OS and DFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“… 20 Moreover, recent studies have reported that the FIGO stage was an independent prognostic factor for the risk of both recurrence and death. 21 , 22 In our study, patients with stage II cervical cancer showed significantly unfavorable OS (HR 2.320 [95% CI: 1.438–3.745]) compared to patients in stage I (data not shown).…”
Section: Discussionmentioning
confidence: 57%
“… 20 Moreover, recent studies have reported that the FIGO stage was an independent prognostic factor for the risk of both recurrence and death. 21 , 22 In our study, patients with stage II cervical cancer showed significantly unfavorable OS (HR 2.320 [95% CI: 1.438–3.745]) compared to patients in stage I (data not shown).…”
Section: Discussionmentioning
confidence: 57%
“…Cervical squamous cell carcinoma (CSCC) is the most common primary tumor in the cervical region; other rare primary tumors include clear-cell carcinoma of the cervix (CCCC) and small-cell carcinoma of the cervix (SCCC), [1][2][3] primary lymphoma of the cervix, 4 cervical choriocarcinoma, 5 sarcoma of the uterine cervix, 6 rhabdomyoma of the cervix, 7 malignant melanoma of the cervix, 8,9 Wilm's tumor of the cervix, 10 and malignant peripheral neurilemmoma of cervical broblasts. 11 Regardless of the type of cervical neoplasm, contact hemorrhage or uor sanguinolentus are the main early clinical manifestations; late clinical manifestations include irregular vaginal bleeding of varying amounts with corresponding symptoms of distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…They occur relatively commonly in the corpus of the uterus but are extremely rare in the cervix, constituting less than 1% of all cervical malignancies . Approximately only 80 cases have been reported in the English literature so far , and 128 cases have been documented according to the National Cancer Institute's Surveillance, Epidemiology, and End Results database . Owing to their rarity, cervical carcinosarcomas have not been well characterized, and currently there is no standard of care for this disease .…”
Section: Introductionmentioning
confidence: 99%
“…Approximately only 80 cases have been reported in the English literature so far , and 128 cases have been documented according to the National Cancer Institute's Surveillance, Epidemiology, and End Results database . Owing to their rarity, cervical carcinosarcomas have not been well characterized, and currently there is no standard of care for this disease . A recent meta‐analysis revealed that the 2‐year disease‐free survival and overall survival were 49% and 60%, respectively .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation